2013
DOI: 10.4067/s0717-95022013000400014
|View full text |Cite
|
Sign up to set email alerts
|

Scopolamine Reduces the Density of M1 Muscarinic Neurons in Rats' Hippocampus

Abstract: JAHANSHAHI, M.; NICKMAHZAR, E. G.; SEIF-HOSEINI, S.; BABAKORDI, F. & MOHARRERI, A.Scopolamine reduces the density of M1 muscarinic neurons in rats' hippocampus. Int. J. Morphol., 31(4):1227-1232, 2013. SUMMARY:Cholinergic system in CNS is involved in learning and memory. Scopolamine as muscarinic acetylcholine receptor antagonist is used for creation of memory impairment. The purpose of this study is evaluation of scopolamine-based amnesia on memory retention and the effect of this phenomenon on the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Consistently with earlier findings [44], our results revealed that treatment of Wistar rats with scopolamine led to decrease M1 muscarinic receptor-ir neuron numbers in the hippocampus. Similarly, after an injection of scopolamine to dogs, the older dogs showed a significant decrease in the density of the muscarinic receptor in some areas of cortex [4].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistently with earlier findings [44], our results revealed that treatment of Wistar rats with scopolamine led to decrease M1 muscarinic receptor-ir neuron numbers in the hippocampus. Similarly, after an injection of scopolamine to dogs, the older dogs showed a significant decrease in the density of the muscarinic receptor in some areas of cortex [4].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the M1 immunoreactivity was markedly decreased in AD brains [85] and also an age-related decrease in the M1 receptor has been reported [91]. Some other researches confirm a scopolamine injection, severe cell losses in hippocampal cholinergic neurons [44,57].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A field of 30,000 µm 2 for CA1 and CA3 areas and also 4800 µm 2 in DG area was selected randomly in the all sections. To measure the area density of the androgen receptor-ir neurons, using OLYSIA Autobioreport software (Olympus, Japan), the appropriate grids were superimposed on the pictures, and the cells were counted manually [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sections were stained with antibody against 5-HT 2A serotonergic receptor, according to our previous report [54] with slight modifications. The sections were first incubated at 37℃ for 30 minutes, then, for deparaffinization, the sections embedded in xylene and hydrated with different degrees of ethanol.…”
Section: Methodsmentioning
confidence: 99%